Application of Microfluidics in Wearable Devices. Issue 12 (11th November 2019) - Chen, Guo; Zheng, Jiangen; Liu, Liyu; Xu, Lei
Abstract: Wearable devices integrated with various electronic modules, biological sensors, and chemical sensors have drawn large public attention. Due to their inherent advantages of superior stretchability, elaborate microstructure, high integration of multiple functions, and low cost, microfluidics are an excellent candidate and have already been widely used in wearable devices. Well‐designed microfluidic devices can realize excellent multiple functions in wearable devices, including sample collecting, handling and storage, sample analysis, signal converting and amplification, mechanic sensing, and power supplying. Moreover, the microfluidic wearable devices with further integration of wireless modules have exhibited potential applications in healthcare monitoring, clinical assessment, and human and intelligent device interaction. This review focuses on the latest advances on multifunctional wearable devices based on microfluidics, primarily including general functions and designs of microfluidic wearable devices, and their specific applications in physiological signal monitoring, clinical diagnosis and therapeutics, and healthcare. Abstract : Microfluidics are widely applied in wearable devices for their inherent advantages. In this review, the general functions and designs of microfluidic‐based wearable devices are summarized in detail. Additionally, some recent progress and main challenges of their applications in specific areas related to physiological signal monitoring, clinical diagnosis and therapeutics, and healthcare are introduced and discussed.